(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Radiation dermatitis remains one of the most common adverse effects of radiotherapy in patients with breast cancer, often leading to discomfort, reduced quality of life, and occasional treatment interruptions. Although technological advances in radiation delivery have improved dose conformity, the incidence of acute skin toxicity remains high. Preventive strategies vary widely across oncology centers, and there is no universally standardized protocol for minimizing radiation-induced skin injury. The present study evaluates the effectiveness of a multimodal preventive approach combining advanced radiotherapy planning, structured patient education, prophylactic skincare regimens, and early dermatologic monitoring.